Cholesterol Mediated Stable Vesicles: A Nano Drug Delivery Vehicle for Anti‐cancer Drugs Curcumin and 5‐Fluorourecil. Issue 33 (1st September 2022) - Ukani, Hiral; Pratyush,; Kumar, Sugam; Aswal, Vinod K; Al‐Ghamdi, Azza A.; Malek, Naved I.
Abstract: Hierarchical self‐assembly of new age surfactants, surface‐active ionic liquids (SAILs) has attracted increasing interests because of its close resemblance to membrane mimetic structure and its application in drug delivery. Among these self‐assembled structures, thermodynamically stable vesicular nanoaggregates are of great importance due to its structure that can carry both, hydrophilic and hydrophobic molecules within its core and bilayers, respectively. Here, we report the ester functionalized SAILs to synergistically interact with cholesterol, the natural sterol to transform the micellar nano‐aggregates to the vesicular nano‐aggregates with outstanding stability with dilution, pH, and temperature. The molecular self‐assembly formed was studied through state of the art analytical techniques including small‐angle neutron scattering (SANS) and fluorescence resonance energy transfer (FRET) upon varying the cholesterol/SAIL ratio. The thermodynamically stable vesicular nano‐aggregates were further used as the nano‐vehicles for the encapsulation and sustained release of the anticancer drugs, curcumin and 5‐flurouracil. Results of the present study could pave way for the realistic drug delivery applications of these thermodynamically stable nano‐aggregates and replace the traditional lipid based vesicle systems. Abstract : Ester functionalized surface active ionic liquids (SAIL)s synergistically interact with cholesterol, the natural sterol, to transform the micellar nano‐aggregates to the vesicular nano‐aggregates with outstanding stability with dilution, pH, and temperature. The molecular self‐assembly formed was studied through state‐of‐the‐art analytical techniques including small‐angle neutron scattering and fluorescence resonance energy transfer upon varying the cholesterol/SAIL ratio.